Genome-wide cooperation of EMT transcription factor ZEB1 with YAP and AP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Bönisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and the EMT-inducing transcription factor ZEB1 is a crucial stimulator of these processes. While work on ZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wide ZEB1 binding study in triple-negative breast cancer cells. We identified ZEB1 as a novel interactor of the AP-1 factors FOSL1 and JUN and show that, together with the Hippo pathway effector YAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression of ZEB1, YAP, FOSL1 and JUN marks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors: ZEB1, AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team Scopus Importer:2020-07-31
Keywords: AP-1; breast cancer; epithelial to mesenchymal transition; ZEB1

Genome-wide cooperation ofEMTtranscription factorZEB1 withYAPandAP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Boenisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and theEMT-inducing transcription factorZEB1 is a crucial stimulator of these processes. While work onZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wideZEB1 binding study in triple-negative breast cancer cells. We identifiedZEB1 as a novel interactor of theAP-1 factorsFOSL1 andJUNand show that, together with the Hippo pathway effectorYAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression ofZEB1,YAP,FOSL1 andJUNmarks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors:ZEB1,AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team WoS Importer:2020-09-25

Interaction modulation through arrays of clustered methyl-arginine protein modifications - Woodsmith, Jonathan; Casado-Medrano, Victoria; Benlasfer, Nouhad; Eccles, Rebecca; Hutten, Saskia; Heine, Christian L.; Thormann, Verena; Abou-Ajram, Claudia; Rocks, Oliver; Dormann, Dorothee; Stelzl, Ulrich (Life Science Alliance, 2018)
Systematic analysis of human arginine methylation identifies two distinct signaling modes; either isolated modifications akin to canonical post-translational modification regulation, or clustered arrays within disordered protein sequence. Hundreds of proteins contain these methyl-arginine arrays and are more prone to accumulate mutations and more tightly expression-regulated than dispersed methylation targets. Arginines within an array in the highly methylated RNA-binding protein synaptotagmin binding cytoplasmic RNA interacting protein (SYNCRIP) were experimentally shown to function in concert, providing a tunable protein interaction interface. Quantitative immunoprecipitation assays defined two distinct cumulative binding mechanisms operating across 18 proximal arginine-glycine (RG) motifs in SYNCRIP. Functional binding to the methyltransferase PRMT1 was promoted by continual arginine stretches, whereas interaction with the methyl-binding protein SMN1 was arginine content-dependent irrespective of linear position within the unstructured region. This study highlights how highly repetitive modifiable amino acid arrays in low structural complexity regions can provide regulatory platforms, with SYNCRIP as an extreme example how arginine methylation leverages these disordered sequences to mediate cellular interactions.
EVALuna2:155437

Non-redundant functions of EMT transcription factors - Stemmler, Marc; Eccles, Rebecca; Brabletz, Simone; Brabletz, Thomas (Nature Cell Biology, 2019)
Epithelial-mesenchymal transition (EMT) is a crucial embryonic programme that is executed by various EMT transcription factors (EMT-TFs) and is aberrantly activated in cancer and other diseases. However, the causal role of EMT and EMT-TFs in different disease processes, especially cancer and metastasis, continues to be debated. In this Review, we identify and describe specific, non-redundant functions of the different EMT-TFs and discuss the reasons that may underlie disputes about EMT in cancer.
EVALuna2:35254

The EMT transcription factor ZEB1 blocks osteoblastic differentiation in bone development and osteosarcoma - Ruh, Manuel; Stemmler, Marc; Frisch, Isabell; Fuchs, Kathrin; van Roey, Ruthger; Kleemann, Julia; Roas, Maike; Schuhwerk, Harald; Eccles, Rebecca; Agaimy, Abbas; Baumhoer, Daniel; Berx, Geert; et al. (Journal of Pathology, 2021)
Osteosarcoma is an often-fatal mesenchyme-derived malignancy in children and young adults. Overexpression of EMT-transcription factors (EMT-TFs) has been associated with poor clinical outcome. Here, we demonstrated that the EMT-TF ZEB1 is able to block osteoblastic differentiation in normal bone development as well as in osteosarcoma cells. Consequently, overexpression of ZEB1 in osteosarcoma characterizes poorly differentiated, highly metastatic subgroups and its depletion induces differentiation of osteosarcoma cells. Overexpression of ZEB1 in osteosarcoma is frequently associated with silencing of the imprinted DLK-DIO3 locus, which encodes for microRNAs targeting ZEB1. Epigenetic reactivation of this locus in osteosarcoma cells reduces ZEB1 expression, induces differentiation, and sensitizes to standard treatment, thus indicating therapeutic options for ZEB1-driven osteosarcomas. (c) 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team WoS Importer:2021-05-14

ZEB1 becomes a transcriptional activator upon interacting with YAP - Lehmann, W.; Eccles, Rebecca; Kleemann, Julia; Mossmann, D.; Meisinger, C.; Mahadevan, V.; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas (2017)
EVALuna2:35505